Upaya Penurunan Kecacatan Mulut Botol Melipat menggunakan Metode DMAIC di PT. XYZ - Jason Fran Tranggono; Prayonne Adi (Jurnal Titra, 2022)
the research was conducted to eliminate the type of folding bottle mouth defect in the production output at PT XYZ. Folding mouth defect is the cause of leakage in the mouth of bottle. The problem is seen based on customer complaint data in 2021-2022, namely 33% of customers complained about leaking bottles. Efforts to eliminate the type of folding mouth defect carried out using the Define, Measure, Analyze, Improve and Control (DMAIC) stages to analyze the root cause of the problem and provide a proposed improvement plan that will be carried out. Analysis of the causes of the problem is done using the help of fishbone diagrams. Four factors cause the problem of folding mouth defects, namely man, machine, method and material factors. Improvements that can be made to eliminate folding mouth defects are to carry out an overall audit of the machine ,replace abnormal parts and making helper tool for set up.